PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEMBIMBING KEMASYARAKATAN DI BAPAS KELAS I MALANG - Kasyfillah, Muhammad; Jarodi, Odi (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of Organizational Culture on Organizational Citizenship Behavior of Community Supervisors at Class I Correctional Center Malang. This is a quantitative research that collects data by distributing questionnaires to 32 respondents who are all Community Supervisors at the Class I Correctional Center in Malang. There are 22 statement items related to the variables studied. The data analysis is carried out with descriptive analysis techniques through simple linear tests, normality tests, significance tests, and determination tests with the help of the IBM SPSS 26 application. The result obtained is the influence of the organizational culture variable on the organizational commitment variable in percentage 49.10% of the R Square. The result shows that there is a positive and significant relationship between Organizational Culture and Organizational Citizenship Behavior of Community Supervisors at Class I Correctional Center Malang. Keywords: Organizational Culture; Community Supervisors; Correctional Institution